Oceanic currents, not land masses, maintain the genetic structure of the mangrove Rhizophora mucronata Lam. (Rhizophoraceae) in Southeast Asia - Wee, Alison K. S.; Takayama, Koji; Asakawa, Takeshi; Thompson, Bijoy; Onrizal,; Sungkaew, Sarawood; Tung, Nguyen Xuan; Salleh@Japri, Mohd Nazre; Soe, Khin Khin; Tan, Hugh T. W.; Watano, Yasuyuki; Baba, Shigeyuki; et al. (Wiley-Blackwell Publishing, 2014)
Aim Mangroves are intertidal plants with sea-dispersed propagules, hence their population structure can offer valuable insights into the biogeographical processes driving population subdivision in coastal species. In this study, we used molecular markers and ocean circulation simulations to examine the effects of ocean currents and land masses on the genetic structure of the major mangrove species Rhizophora mucronata. Location Southeast Asia. Methods We assessed the genetic structure of 13 R. mucronata populations from continental Southeast Asia and Sumatra using 10 microsatellite loci. We first examined the relative effects of geographical distance and land mass (the Malay Peninsula) in shaping the genetic structure of R. mucronata in Southeast Asia. We then characterized the genetic structure of R. mucronata and compared it to the simulated ocean circulation patterns within our study region. Results Despite the low genetic diversity, significant genetic structuring was detected across R. mucronata populations. Contrary to observations on other mangrove species, genetic differentiation in R. mucronata was not found across the coasts of the Malay Peninsula, nor was it correlated with geographical distance. Instead, the most distinct genetic discontinuity was found at the boundary between the Andaman Sea and the Malacca Strait, and this can be explained by the prevailing ocean currents in this region. Main conclusions Our study presents novel evidence that the genetic structure of R. mucronata is maintained by ocean current-facilitated propagule dispersal.